Back Cover: Photoelectroreduction of Building‐Block Chemicals (Angew. Chem. Int. Ed. 25/2017). Issue 25 (9th May 2017) - Chen, Fengjiao; Cui, Wei; Zhang, Jie; Wang, Yeyun; Zhou, Junhua; Hu, Yongpan; Li, Yanguang; Lee, Shuit‐Tong
Abstract : Down to the wire : A silicon nanowire array photocathode mediates photoelectroreductive transformation of maleic and oxalic acids into building‐block chemicals. In their Communication onpage 7181 ff., Y. G. Li et al. report a large photovoltage generated from the semiconductor/electrolyte junction of the photocathode, which is used to offset the external bias required by electroreduction. The photoelectrosynthetic approach is selective for succinic and glyoxylic acids.